Reviewing operational performance changes from Automation and Robotization in warehousing - Omarov, Assylbek; Martínez, Felipe; Jirsák, Petr; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
The rapid evolution of warehousing from manual, paper‐based operations to technology‐driven environments poses both opportunities and uncertainties for managers seeking to balance quality, speed, dependability, flexibility, and cost. Yet few studies have offered a structured, operations‐focused comparison of emerging warehouse technologies against a purely manual baseline. This thesis addresses that gap by evaluating how seven leading automation and robotization solutions are expected to impact the five core performance objectives relative to a baseline scenario. These technologies were assessed based on mixed-method approach and scored using Likert instrument and nonparametric analyses included the Friedman omnibus test and Wilcoxon signed-rank tests for pairwise comparisons. This thesis offers a comprehensive review of current innovations and a grounded evaluation method. This structured evaluation offers practical, evidence-based guidance for firms planning warehouse technology adoption. The results underscore improvements in one operational dimension often come with trade-offs with other performance objectives and that technology should complement, not replace, strong foundations and continuously improve the operating and fix underlying bottlenecks.
Vedoucí práce: Felipe Martínez
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses